Analysis and simulation of asymmetrical nanoscale self-switching transistor. (3rd September 2022) - Horri, Ashkan; Faez, Rahim
ABSTRACT: In this paper, we present a computational study on the electrical behaviour of self-switching transistors (SSTs) based on InGaAs/InP heterojunction. Our simulation is based on the solution of Poisson and Schrodinger equations self-consistently by using Finite Element Method (FEM). By using this method, electrical characteristics of device, such as I O N / I O F F ratio, subthreshold swing, and intrinsic gate-delay time are investigated. Also, the effects of geometrical variations on the electrical parameters of SSTs are simulated. We show that appropriate design of the device allows current modulation exceeding 10 5 at room temperature.